Role of NKT Cells in the Pathogenesis of NAFLD - Kazuto Tajiri; Yukihiro Shimizu (International Journal of Hepatology)
Nonalcoholic fatty liver disease (NAFLD) is the most frequent chronic liver disease and shows various inflammatory changes in the liver. Among those inflammatory cells, natural killer T (NKT) cells are found to have a critical role during the disease progression. NKT cells may have a protective role at the early stage with simple steatosis through modification of insulin resistance, whereas they act as a progression factor at the advanced stage with fibrosis. Those processes are thought to depend on interaction between NKT cells and CD1d molecule in the liver.